Enhancing Digital Wallet Services Based on Electronic Word of Mouth Using Social Media Reviews - Rahmat Nurcahyo; Anton Satria Prabuwono; Intan Novita Dewi; Farizal; Nurhadi Wibowo; Muhammad Habiburrahman; Khairi Hindriyandhito; Yeong Min Jang (SAGE Open)
The rapid increase in cashless transactions, especially digital wallets that have become widely used, has increased competition among service providers. However, while competitive analysis in this field has been explored extensively, there is still a gap regarding analyzing user feedback through social media channels. This research aims to address this gap by evaluating the competition of digital wallet providers in Indonesia, explicitly focusing on user feedback from Twitter (X), a well-known platform for its role in electronic Word of Mouth (e-WOM). This research employs SERVQUAL framework to analyze reviews of Indonesia's leading digital wallet providers, LinkAja and DANA. Support Vector Machine (SVM) and and K-Nearest Neighbors (KNN) were used for sentiment analysis by categorizing user feedback into reliability, economic benefits, assurance, and responsiveness. The findings show that LinkAja is better in responsiveness dimension while DANA is better in economic benefit dimension the quality of services, as evidenced by a higher volume of positive reviews. This research underscores the critical role of social media reviews in assessing user satisfaction and provides actionable insights for digital wallet providers to improve service quality. This research contributes to the literature by offering a novel application of e-WOM analysis in the competitive evaluation of digital wallet services.